Respons dan Kesiapan Guru Yayasan Madrasah Islamiyah Wonopringgo dalam Menghadapi Kurikulum Merdeka - Murodah, Nelli; Gunawan, Muhammad Ali (IEMJ: Islamic Education and Management Journal, 2024)
This study aims to analyze the response and readiness of teachers of Yayasan Madrasah Islamiyah (YMI) Wonopringgo in facing the independent curriculum. Data were collected through in-depth interviews, participatory observation, and documentation studies. Data analysis used an interactive analysis model proposed by Miles and Hubermen. The results show that the response of teachers in the Yayasan Madrasah Islamiyah (YMI) Wonopringgo is different. While in readiness, it shows that there is no mature readiness made by teachers in the Yayasan Madrasah Islamiyah (YMI) Wonopringgo in facing the independent curriculum.